Spermatogenic Waves and Expression of AR and ERs in Germ Cells of Podarcis sicula - Verderame, Mariailaria; Angelini, Francesco; Limatola, Ermelinda (International Journal of Zoology, 2014)
Androgens are considered the main hormones that regulate spermatogenesis, but a lot of evidence confers to estrogen a key role in this process. In the testis of the seasonal breeder lizard Podarcis sicula we analyzed by means of in situ hybridization the expression of the androgen receptor (AR) and of the two types, α and β, of the estrogen receptors (ERs) throughout the three periods of the annual cycle: mating (spring-early summer), postmating-refractory (late summer), and autumnal recrudescence. The results show that during the mating period AR and ERs are expressed in all germ cells present in the tubules from spermatogonia to spermatozoa. During the postmating-refractory period, when only spermatogonia are present in the tubules, almost all express ERs and very few AR mRNA. During the autumnal recrudescence the localization of AR and ERs is the same of the mating period except for the population of the primary spermatocytes. The expression of the investigated receptors is peculiar in these cells that are positive in the middle-late pachytene stage of the meiotic prophase and negative in preleptotene. A possible functional role of the observed differences during spermatogenesis and in the spermatozoa is also discussed.